Synergism in novel silver-copper/hydroxyapatite composites for increased antibacterial activity and biocompatibility - Olivas Armendariz, Imelda; Martínez-Gracida, Nabor; Esparza-González, Sandra Cecilia; Castillo Martínez, Nydia Alejandra; Serrano-Medina, Araceli; Campos Múzquiz, Lizeth Guadalupe (2020)
This study develops a novel silver-copper/hydroxyapatite composite (Ag–Cu/HA) with high biocompatibility and antibacterial activity. Two different materials were synthesized, namely silver-hydroxyapatite (Ag-HA) and copper-hydroxyapatite (Cu-HA) composites, with 0.1%, 0.5%, and 1.0% (mol) of each metal. These materials were mixed in a planetary mill to obtain the Ag–Cu/HA composites. The results of our characterization demonstrated the low cytotoxicity and hemolytic response. The composite showed higher percent-inhibition for bacterial growth compared to those in separated composites of silver or copper with hydroxyapatite. Hence, these new materials promise higher efficacy as antibacterial hydroxyapatites.